Circulating CD62E+ Microparticles and Cardiovascular Outcomes - Lee, Soon-Tae; Chu, Kon; Jung, Keun-Hwa; Kim, Jeong-Min; Moon, Hye-Jin; Bahn, Jae-Jun; Im, Woo-Seok; Sunwoo, Junsang; Moon, Jangsup; Kim, Manho; Lee, Sang Kun; Roh, Jae-Kyu (PLOS ONE, 2012)
Background Activated endothelial cells release plasma membrane submicron vesicles expressing CD62E (E-selectin) into blood, known as endothelial microparticles (EMPs). We studied whether the levels of endothelial microparticles expressing CD62E+, CD31+/Annexin-V+, or CD31+/CD42− predict cardiovascular outcomes in patients with stroke history. Methods/Principal Findings Patients with stroke history at least 3 months prior to enrolment were recruited. Peripheral blood EMP levels were measured by flow cytometry. Major cardiovascular events and death were monitored for 36 months. Three hundred patients were enrolled, of which 298 completed the study according to protocol. Major cardiovascular events occurred in 29 patients (9.7%). Nine patients died, five from cardiovascular causes. Cumulative event-free survival rates were lower in patients with high levels of CD62E+ microparticles. Multivariate Cox regression analysis adjusted for cardiovascular risk factors, medications and stroke etiologic groups showed an association between a high CD62E+ microparticle level and a risk of major cardiovascular events and hospitalization. Levels of other kinds of EMPs expressing CD31+/Annexin-V+ or CD31+/CD42− markers were not predictive of cardiovascular outcomes. Conclusion A high level of CD62E+ microparticles is associated with cardiovascular events in patients with stroke history, suggesting that the systemic endothelial activation increases the risk for cardiovascular morbidities.